La Vie métrique de saint Laumer (BHL 4735) copiée par Orderic Vital - Hincker, Monique (Analecta Bollandiana, 2006)
The metrical Vita of Saint Launomar copied by Ordericus Vitalis faithfully adapts the legendary prose account of the Vita of the founder of the monastery of Corbion in the region of Perche (Orne, France) in the 6th century (BHL 4734). The alterations are merely literary and stylistic. On the basis of a metrical analysis the poem can be dated to the late 11th century at the scriptorium of Saint-Évroult but Ordericus does not seem to be the author.